2017
DOI: 10.1021/acs.energyfuels.7b01634
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Kinetic Model for Biomass Pyrolysis at Gasification Conditions

Abstract: Computational fluid dynamics (CFD) tools are increasingly gaining importance to obtain detailed insight into biomass gasification. A major shortcoming of the current CFD tools to study biomass gasification is the lack of computationally affordable chemical kinetic models, which allows detailed predictions of the yield and composition of various gas and tar species in complex reactor configurations. In this work, a detailed mechanism is assembled from the literature and reduced to a compact model describing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
(80 reference statements)
0
21
0
Order By: Relevance
“…A (fast) pyrolysis process transforms the biomass, in the absence of oxygen, into noncondensable gases (like CO, CO 2 , and H 2 ), tar or bio-oil, and biochar or solid carbon. (Fast) pyrolysis processes occur at relatively low temperatures (between 300 and 600 • C) and are characterized by a high liquid fuel yield, i.e., bio-oil (Anca-Couce and Scharler, 2017; Goyal and Pepiot, 2017). Bio-oil is considered to be a suitable replacement for fossil fuels and displays many advantageous properties, like its ease of storing and transportation (Cai et al, 2018).…”
Section: Thermochemical Conversion Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…A (fast) pyrolysis process transforms the biomass, in the absence of oxygen, into noncondensable gases (like CO, CO 2 , and H 2 ), tar or bio-oil, and biochar or solid carbon. (Fast) pyrolysis processes occur at relatively low temperatures (between 300 and 600 • C) and are characterized by a high liquid fuel yield, i.e., bio-oil (Anca-Couce and Scharler, 2017; Goyal and Pepiot, 2017). Bio-oil is considered to be a suitable replacement for fossil fuels and displays many advantageous properties, like its ease of storing and transportation (Cai et al, 2018).…”
Section: Thermochemical Conversion Platformsmentioning
confidence: 99%
“…Bio-oil is considered to be a suitable replacement for fossil fuels and displays many advantageous properties, like its ease of storing and transportation (Cai et al, 2018). Gasification processes are in their essence pyrolysis processes, but occur at higher temperatures (800-1,200 • C) and mostly in the presence of oxygen (Goyal and Pepiot, 2017;Jin et al, 2017). Because of the higher process temperatures, the yield of gaseous products is higher than in the case of pyrolysis processes.…”
Section: Thermochemical Conversion Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the processes of heat and mass transfer, thermodynamic and chemical processes have to be adequately addressed in the models. The equilibrium [8][9][10] and kinetic [11][12][13] approaches are used in most known models. Many kinetic models are based on the concept of a perfectly stirred reactor, considering detailed mechanisms of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Most EL studies to date consider two‐dimensional flows with a relatively small number of particles (e.g., Refs. ). Recent work has demonstrated that two‐dimensional simulations are only capable of capturing qualitative features of particle clustering, and a fully three‐dimensional description is required to accurately capture the quantitative flow behavior in CFB risers.…”
Section: Introductionmentioning
confidence: 99%